Relative sensitivities of forward and reverse mutation assays in Salmonella typhimurium. - Skopek, T R (1978)
Forward mutation to 8-azaguanine resistance and reverse mutation to histidine prototrophy were measured in Salmonella typhimurium after treatment with 16 mutagens of both base-substitution and frameshift classes. The two approaches were found to be equisensitive for all 16 mutagens--i.e., induction of significant mutation occurred at similar concentrations in the forward mutation assay and in the most sensitive of the five Ames tester strains.